Association Between Impaired Vα7.2+CD161++CD8+ (MAIT) and Vα7.2+CD161-CD8+ T-Cell Populations and Gut Dysbiosis in Chronically HIV- and/or HCV-Infected Patients - Merlini, Esther; Cerrone, Maddalena; van Wilgenburg, Bonnie; Swadling, Leo; Cannizzo, E. Stefania; d’Arminio Monforte, Antonella; Klenerman, Paul; Marchetti, Giulia (Frontiers in Microbiology, 2019)
Both HIV and HCV infections feature increased microbial translocation (MT) and gut dysbiosis that affect immune homeostasis and disease outcome. Given their commitment to antimicrobial mucosal immunity, we investigated mucosal-associated invariant T (MAIT) cells and Vα7.2+CD161- T-cell frequency/function and their possible associations with MT and gut dysbiosis, in chronic HIV and/or HCV infections. We enrolled 56 virally-infected (VI) patients (pts): 13 HIV+ on suppressive cART (HIV-RNA<40cp/ml), 13 HCV+ naive to DAA (direct-acting antiviral) anti-HCV agents; 30 HCV+/HIV+ on suppressive cART and naive to anti-HCV. 13 age-matched healthy controls (HC) were enrolled. For Vα7.2+CD161++ and Vα7.2+CD161- CD8+ T cells we assessed: activation (CD69/CD39), exhaustion (PD1), and cytolytic activity (granzymeB/perforin). Following PMA/ionomycin and E. coli stimulation we measured intracellular IL17/TNFα/IFNγ. Markers of microbial translocation (Plasma LPS, 16S rDNA, EndoCAb and I-FABP) were quantified. In 5 patients per group we assessed stool microbiota composition by 16S targeted metagenomics sequencing (alpha/beta diversity, relative abundance). Compared to controls, virally-infected pts displayed significantly lower circulating Vα7.2+CD161++CD8+ MAIT cells (p=.001), yet expressed higher perforin (p=0.004) and granzyme B (p=0.002) on CD8+ MAIT cells. Upon E. coli stimulation, the residual MAIT cells are less functional particularly those from HIV+/HCV+ patients. Conversely, in virally-infected pts, Vα7.2+CD161-CD8+ cells were comparable in frequency, highly activated/exhausted (CD69+: p=0.002; PD-1+: p=0.030) and with cytolytic potential (perforin+: p<0.0001), yet were poorly responsive to ex vivo stimulation. A profound gut dysbiosis characterized virally-infected pts, especially HCV+/HIV+ co-infected patients, delineating a Firmicutes-poor/Bacteroidetes-rich microbiota, with significant associations with MAIT cell frequency/function. Irrespective of mono/dual infection, HIV+ and HCV+ patients display depleted, yet activated/cytolytic MAIT cells with reduced ex vivo function, suggesting an impoverished pool, possibly due to continuous bacterial challenge. The MAIT cell ability to respond to bacterial stimulation correlates with the presence of Firmicutes and Bacteroidetes, possibly suggesting an association between gut dysbiosis and MAIT cell function and posing viral-mediated dysbiosis as a potential key player in the hampered anti-bacterial MAIT ability.